PENGARUH PEMBELAJARAN ONLINE, EFIKASI DIRI, DAN MOTIVASI BELAJAR TERHADAP STRES AKADEMIK MAHASISWA DI MASA PANDEMI COVID-19 (STUDI PADA MAHASISWA JURUSAN MANAJEMEN ANGKATAN 2017-2020) - ,Arwinance Pramadewi, Iswatul Husna , Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of self-efficacy online learning and learning motivation on the academic stress of students majoring in Management class of 2017-2020, University of Riau. The population in this study included all students majoring in Management class 2017-2020, faculties of economics and business, totaling 1181 people with a sample of 92 people using the slovin formula. This study used a quantitative descriptive method with multiple linear regression analysis tools with the help of SPSS version 25. The results showed that 1. There is a positive and significant effect between online learning on student academic stress. 2. There is a negative and significant effect between self-efficacy and student academic stress. 3. There is no effect between learning motivation and student academic stress. Keywords: Online Learning, Self-Efficacy, Learning Motivation and Student Academic Stress